Coaching with research in mind - Jones, Rebecca J. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
How can coaches maximise the effectiveness of their practice? What can research tell us about how and why coaching works'? How can we use the evidence base to enable others to reach their full potential? Coaching with Research in Mind brings together cutting-edge research in coaching and psychology, accessibly summarises the findings, and provides a clear and specific breakdown of what research tells us coaches and leaders should be doing and why. Rebecca J. Jones provides practitioners with the information and guidance they need to apply research in their practice, explaining how coaches can understand coachee characteristics, how they impact the coaching process and how coaches should adapt their practice to accommodate them. The book explains how to identify which principles of the coaching process influence effectiveness and tailor practice to maximise their impact. Jones also explores the impact of environmental factors and assesses how their influence can be limited. Coaching with Research in Mind will be essential reading for both new and experienced coaches looking to enhance the effectiveness and impact of their coaching, and for managers, leaders and L&D procurers who utilise coaching as a leadership style.
OCLC-licensed vendor bibliographic record.
Keywords: Executive coaching -- Research; PSYCHOLOGY / Industrial & Organizational Psychology; PSYCHOLOGY / Mental Health